ANALISIS STRUKTURAL GENETIK PADA NOVEL ROGUE LAWYER KARYA JOHN GRISHAM: ANALISIS SOSIOLOGI SASTRA - Sinubu, Rangga Johan Zefanya; Sigarlaki, Stephani J.; Lotulung, Donald R. (JURNAL ELEKTRONIK FAKULTAS SASTRA UNIVERSITAS SAM RATULANGI, 2022)
Â  Â  Â  Â  Â  Â  Â  Â  Â  Â  Â  Â  Â  Â  Â  Â  Â  Â  Â  Â  Â  Â  Â  Â  Â  Â  Â  Â  AbstractÂ  Â  Â This research entitled â€œGenetic Structural Analysis on Novel Rogue Lawyer by John Grisham: An Analysis of Sociological Literatureâ€. The focus of this research is a sociological analysis on Rogue Laywer. It is showing the social structure and authorâ€™s idea reflected in imaginary world using genetic structuralism theory. In this analysis, the writer attempts to analyze the social structure and authorâ€™s idea by looking at the characters, plot, setting. The data were collected from the novel Rogue Lawyer. The writer uses the theory of Literature by Wellek and Warren (1956) in order to analyze the intrinsic approach. He also uses Lucien Goldmann (1980) theory about genetic structuralism, and Ashley Crossman theory about social structure (2019) to analyze the extrinsic approach. The method employed in this research is descriptive method. The result of this study shows that there are three social structures included in the novel, those are law and law enforcement, social structure of family, also about upper class and lower class. Imaginary world of the author also reflected his idea about society, those are law and justice, narration and power, and Grishamâ€™s ideas about social classKeywords: Genetic Structuralism, Novel Rogue Lawyer, Analysis, Sociological Literature